Influence of temperature and ultrasound on drying kinetics and antioxidant properties of red pepper. Issue 4 (12th March 2019) - Cárcel, J. A.; Castillo, D.; Simal, S.; Mulet, A.
Abstract: Red pepper samples (1 m/s) were dried at different temperatures (30, 50, 70 °C) without and with (20.5 kW/m 3 ; 21.7 kHz) ultrasound application. The antioxidant capacity (AC), the total phenolic content (TPC), and the ascorbic acid (AA) content of fresh and dried red pepper samples were used as indicators of the quality of the dried products. Ultrasound application significantly improved the kinetics in every case, influencing not only the effective diffusivity but also the mass transport coefficient thus implying a reduction in energy needs. Drying significantly reduced AC, TPC, and AA, this reduction being significantly smaller at 70 °C due to the shorter drying time. Compared with conventional drying, ultrasound application reduced the loss of antioxidant properties at 50 °C but produced greater degradation at 70 °C, which points toward an optimal drying temperature when using ultrasound.